Raspadinha digital para interação entre professores e alunos por Team-Based Learning - Klososki, Patrick James (2017)
The active methodologies are important resources for the critical and reflexive formation of students through constructivist learning teaching processes, which highlight the contemporary context of teaching when they favor the students’ autonomy and curiosity. Adopting an active methodology is still a great challenge, as they struggle with relationships of culture, resistance, ignorance and denial for not wanting to try to impose something new. In this context, the Team-Based Learning (TBL) method can be offered, together with the help of the feedback card ("in a simpler translation of the scratch cards"), which is a proposal to unite and interact teachers and students in classroom. Thus, the objective of this work is to enable a model of pedagogical practice based on the active TBL methodology for the mediation of its varied contents developed in the classroom. The objective of the work is to develop a policy for smartphones that implements the active TBL methodology for student - content mediation. This application will be a "Digital Scratch", will give immediate feedback.